2022
DOI: 10.1007/s41742-022-00462-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of SARS-CoV-2 Genome in the Indoor Air and High-Touch Surfaces

Abstract: This study aimed to investigate the presence/absence of SARS-CoV-2 genome in the air and high-touch surfaces. This cross-sectional study was conducted from late-2020 to mid-2021 in the sections of Intensive Care Unit (ICU), emergency, infectious disease ward, and nursing station of the COVID-19 patient reception center in Kerman, Iran. The presence/absence of SARS-CoV-2 genome in the 60 samples of high-touch surfaces and 23 air samples was analyzed by reverse transcription polymerase chain reaction (RT-PCR). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This is essential to better understand viral resistance to environmental stress, inform on the risks of acquisition in the community and occupational environments and appropriately evaluate virus mitigation methods in indoor settings. Several studies have reported the presence of SARS-CoV-2 RNA in air samples in various settings such as long-term care, acute and intensive care, cars and homes [2][3][4][5]. Unlike molecular methods that allow the quantification of viral genome in air samples, measuring infectious viral particles that may contribute to SARS-CoV-2 transmission is not trivial and has been a technical challenge knowing that the samplers, the environmental context, the time of sampling and the need to store the samples before analysis can strongly influence the quantity of viral particles collected as well as their infectivity [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is essential to better understand viral resistance to environmental stress, inform on the risks of acquisition in the community and occupational environments and appropriately evaluate virus mitigation methods in indoor settings. Several studies have reported the presence of SARS-CoV-2 RNA in air samples in various settings such as long-term care, acute and intensive care, cars and homes [2][3][4][5]. Unlike molecular methods that allow the quantification of viral genome in air samples, measuring infectious viral particles that may contribute to SARS-CoV-2 transmission is not trivial and has been a technical challenge knowing that the samplers, the environmental context, the time of sampling and the need to store the samples before analysis can strongly influence the quantity of viral particles collected as well as their infectivity [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among these human HCoVs, four of them including HCoV-OC43, HCoV-229E, HCoV-HKU1, and HCoV-NL63 usually lead to mild to moderate respiratory diseases. SARS-CoV-2 has the third known zoonotic virus, which was spread after SARS-CoV-1 and MERS [1][2][3][4] . It is reported that SARS-CoV-2 encodes more than seven accessory proteins (ORF3a, ORF3b, ORF6, ORF7a, ORF7b, ORF8, and ORF9b), and it should be mentioned that this virus encodes ORF9c and ORF10, which play a role in the immune evasion process 5 .Based on the situation report of WHO, until November 9, 2022, there have been 630,387,858 confirmed cases of COVID-19 (SARS-CoV-2) including 6,583,163 deaths worldwide.…”
mentioning
confidence: 99%